Changes of visualised Eustachian tube lengths by age and position: Radiologic study in sitting and supine positions using cone beam and conventional CT. (2nd May 2019) - Ha, Seung Cheol; Baik, Jin; Park, Hyo Jung; Moon, Hyun; Kang, Byung Chul; Park, Jun Woo; Kang, Woo Seok; Park, Hong Ju
Abstract: Objectives: Patulous eustachian tube (ET) has been characterised by the visualisation of full‐length ET on computed tomography (CT) results. We wanted to investigate the changes of visualised ET lengths by age in supine and sitting positions. Design: Retrospective study. Setting: Tertiary care academic referral centre. Participants: One hundred subjects who underwent cone beam CT (CBCT) in a sitting position and conventional CT in a supine position for non‐otitis‐related or dental complaints. Main outcome measures: Visualised ET lengths from the nasopharyngeal orifice measured by different positions and ages. Results: Subjects did not show visualisation of full‐length ET throughout the study. The visualised ET lengths (9.0 ± 2.5 mm) of the CBCT group were significantly larger than those (6.8 ± 2.3 mm) of the conventional CT group ( P  < 0.0001).Women showed longer visualised ET lengths than men in CBCT group ( P  < 0.001). The visualised ET lengths of the CBCT group were consistent or slightly increasing as a function of age ( P  = 0.06); however, the visualised ET lengths of the conventional CT group decreased as a function of age ( P  = 0.001). The slopes of regression lines of the two groups were significantly different. Conclusions: When in the supine position, the ET lengths gradually shortened as the subjects got older, most likely due to venous engorgement and the collapse of surrounding tissues; this finding thus suggests that CT in a supine position is an inappropriate method to diagnose patulous ET. The visualised ET lengths by CBCT in a sitting position were consistent throughout the different ages of the subjects and may be used as a diagnostic test for patulous ET.